Juridish Review of Law No. 23 of 2004 concerning the Elimination of Domestic Violence of Household in Biak Numfor Regency - Luluk Endang Nurrokhmah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to determine the law enforcement of Law No. 23 of 2004 concerning the Elimination of Domestic Violence in North Minahasa Regency and to find out efforts to optimize the enforcement of Law No. 23 of 2004 concerning the Elimination of Domestic Violence in North Minahasa Regency. The population in this study are perpetrators of domestic violence crimes, the community and all parties involved in law enforcement of the Law on the Elimination of Domestic Violence. The sample in this study was taken purposively (purposive sampling) on the population, including law enforcement officers consisting of police, prosecutors and judges as well as the community in Biak Numfor Regency. The data collected is then analyzed qualitatively, namely the analysis that describes the data obtained, both primary data and secondary data, then made interpretations for decision making. The results of this study indicate that the prevalence of violence is closely related to the aggressive nature of living things including humans to defend themselves in order to survive, besides that the occurrence of violence has strong roots in materialist mindsets and selfish attitudes, so that violence has become a social phenomenon that occurs everywhere, both in both urban and rural communities. Violence against fellow human beings seems to know no boundaries of space and time. Violence does not only occur in public spaces, but also occurs in domestic spaces.